An Infant's Question on COVID-19 and Music: Should I Attend My Online Classes? - Papatzikis, Efthymios (Frontiers in Psychology, 2021)
In the past few months, we faced a profound challenge to balance our lives amidst fighting the COVID-19 virus. The reactions to this coronavirus pandemic have no doubt affected all aspects of our everyday normalcy as they have called for an extended set of measures that have greatly impacted our social interactions and well-being. During this unprecedented global situation, the pandemic has also taken its toll on education, as schools, universities and other educational institutions have suspended their programs or moved online to retain educational momentum. Among the programs that tried to adapt to this online model was the early years music education. This mini-review article aims to discuss the framework of online existence for the early years music programs amid the COVID-19 crisis, while considering their benefits and character under these extraordinary circumstances.